Creation of a content proposal for the IIHF Player Development Guide - Lundman, N. (Haaga-Helia University of Applied Sciences, 2018)
The International Ice Hockey Federation (IIHF) is the international governing body of ice hockey and inline hockey. The IIHF has 76 member associations and each of these members is the governing body of the sport in its nation. The IIHF is devoted to the global development and promotion of these two sports by assisting its member associations. The objectives of this research are, to provide reasoning for the IIHF for investing resources into the process of developing a long-term player development framework for its member National associations as well as to come up with a suggestion for the content of the framework. The research questions relate to the need and to the content of the framework. The name of the framework is: IIHF Player Development Guide. This research consists of an examination process into the Long-Term Athlete Development Model, a quantitative research and a benchmarking process. The examination process into the Long-Term Athlete Development Model, provides knowledge on the process of longterm player development, which is important in the process of analysing the results of the quantitative research and the benchmarking process. The quantitative research and the benchmarking process provide answers on the research questions and research objectives. The research resulted in providing a reasoning for the IIHF Player Development Guide and a suggestion for the content of the guide, both based on the results from the quantitative research and the benchmarking process. The results provide understanding on, why the global governing body of ice hockey should produce a long-term player development framework for its member National associations and what should be included in such a framework.